Measuring trends in leisure: The allocation of time over five decades - Mark Aguiar; Erik Hurst (Federal Reserve Bank of Boston, 2006)
In this paper, we use five decades of time-use surveys to document trends in the allocation of time. We document that a dramatic increase in leisure time lies behind the relatively stable number of market hours worked (per working-age adult) between 1965 and 2003. Specifically, we document that leisure for men increased by 6?8 hours per week (driven by a decline in market work hours) and for women by 4?8 hours per week (driven by a decline in home production work hours). This increase in leisure corresponds to roughly an additional 5 to 10 weeks of vacation per year, assuming a 40-hour work week. We also find that leisure increased during the last 40 years for a number of sub-samples of the population, with less-educated adults experiencing the largest increases. Lastly, we document a growing inequality in leisure that is the mirror image of the growing inequality of wages and expenditures, making welfare calculation based solely on the latter series incomplete.
Keywords: D12; D13; J22; 330; Zeitverwendung; Freizeit; Arbeitszeit; USA